Evaluasi Pelaksanaan Program Pendidikan Inklusi di SMP Negeri - Mariani, Eni; Sulasmono, Bambang Suteng (Universitas Kristen Satya Wacana, 2018)
This study aims to evaluate the design, installation, process, and products of the inclusive education program implementation in a Salatiga Public Middle School. This type of research is program evaluation with a discrepancy evaluation model. Information sources in this study are the Principal, Local Content Teacher, Counseling Guidance Teacher who also acts as Special Facilitators Teacher (GPK). Data collection technique include interviews, observation and document study. Data analysis technique include data collection, data reduction, data presentation, and conclusion drawing. Data validation through technical and source triangulation. The results: (1) the design evaluation showed the general curriculum and assessment plans have not been modified, educators do not yet have adequate competence, facilities and infrastructure do not yet support the needs of special needs student (ABK); (2) the installation evaluation showed there is no entrance test, the learning design and assessment have not considered the existence of ABK, funding is taken from BOS funds and support from some ABK parents; (3) the process evaluation showed the ABK have difficulty following learning, the support from the community and agencies has not been maximized; and (4) the product evaluation showed that student learning outcomes, namely the assessment of student ID cards are still equated with normal students. Based on the results of the evaluation, the researchers gave the following recommendations: 1) Teachers and GPK collaborated in developing curriculum and competencies, 2) Principals and teachers collaborated in designing models and technical instructions to handle ABK, as well as increasing collaboration with several agencies, and 3) The education office needs to pay attention to the implementation of inclusive education programs and provide assistance in the form of costs, training, seminars, and fulfillment of facilities and infrastructure.